Noninvasive prenatal testing of beta-thalassemia for common Pakistani mutations: a comparative study using cell-free fetal DNA from maternal plasma and chorionic villus sampling. Issue 1 (31st December 2022) - Afzal, Muhammad; Naeem, Muhammad Abdul; Ahmed, Suhaib; Amin, Nayyar; Rahim, Amena; Munawar, Manazza; Ishaq, Mansoor; Rathore, Ali; Maria, K.
ABSTRACT: Background: The discovery of circulating cell-free fetal DNA (cff-DNA) in maternal plasma has inspired the noninvasive prenatal testing (NIPT) approaches for various genetic fetal screening including rhesus D typing, sex determination, aneuploidies, and single-gene disorders. Objective: Noninvasive determination of paternally inherited beta-thalassemia mutations in maternal total cell-free DNA (cf-DNA) by using allele-specific amplification refractory mutation system (ARMS) real-time PCR (RT-PCR) in concordance with the conventional invasive method. Methods: An observational study was conducted at the Armed Forces Institute of Blood Transfusion in collaboration with the genetics resource center from March 2021 to August 2021. A total number of 26 couples were selected having a history of previously affected children with beta-thalassemia. A routine chorionic villus sampling (CVS) invasive procedure was carried out, and the mutation analysis was done using conventional PCR. To assess NIPT, a total cf-DNA was also extracted from maternal plasma and analyzed using allele-specific ARMS RT-PCR. Results: Based on conventional PCR testing, 13 of 26 couples were found having beta-thalassemia carriers with homozygous mutation, and 13 couples were carriers with heterozygous mutations. Further to assess NIPT, the cf-DNA of 13 pregnant females among the couples with different mutational patterns was analyzed by allele-specific ARMS RT-PCR to detect paternally inherited mutations. In comparison with conventional PCR, 11 cases (84.6%) were matched successfully, while two cases (15.4%) had no concordance with conventional invasive prenatal testing (IPT). Conclusion: NIPT using maternal cf-DNA by allele-specific ARMS RT-PCR can be feasible to screen paternal inherited mutant alleles to rule out pregnant women from invasive procedures where the test would be negative for paternal inheritance. However, a low amount of fetal DNA in maternal plasma is a limiting factor and required further improvement to enrich fetal cf-DNA for complete concordance with conventional IPT.